Integrity verification for an optimized cloud architecture - Ahmed, Iqbal; Alam, Fahim Irfan (Universitas Ahmad Dahlan, 2020)
Cloud computing has significantly benefited todays environment of IT industry through its mobility, sustainability, security, cost savings and several other important features. The risk of data loss on cloud in case of dealing with hardware and software is relatively small. However, the issue of data security becomes imminent when we are storing personal data on the cloud which is not transparent to users. In this paper, we introduce a new entity in terms of a virtual machine that provides services and assurance beyond service level agreement (SLA). In the proposed model, a role of data handling and security is assured with association of third party auditor (TPA) by the virtual machine. We further demonstrate the applied technique for encryption, decryption and integrity verification modules. We also upgrade the entropy of the advanced encryption standard (AES) with a variant of secret sharing scheme in the environment of cloud simulator.